Complete mitochondrial genome of Ciconia nigra (Ciconiiformes: Ciconiidae). Issue 1 (1st January 2017) - Lee, Mu-Yeong; Jeon, Hey Sook; Kim, Young-Jun; An, Junghwa
Abstract: The complete mitogenome of the Black Stork Ciconia nigra, obtained using a PCR-based method, is reported. It is 17, 905 bp, slightly A + T biased (30.8% A, 31.5% C, 14.1% G, and 23.6% T), and comprises 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and 1 putative non-coding gene. The two kinds of tandem repeat units found in D-loop (2316 bp) generated a length polymorphism between this and the previously reported D-Loop of C. nigra from China (2206 bp). A frameshift mutation was observed in ND3 . The phylogenetic analysis clustered C . nigra with other Ciconia species.